ANALISIS PERKEMBANGAN PAJAK HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) (STUDI KASUS: KABUPATEN SEKADAU MELALUI ANALISIS SWOT) - B21109022, STANESLAOS KEDI KEDI (Jurnal Pembangunan dan Pemerataan, 2015)
The subject matter of this paper is to discuss about the hotel and restaurant tax contribution to regional revenue and business development and resroran hotel in Sekadau over the last six years, namely from 2008 to 2013. The purpose of this paper is to analyze the contribution of hotel and restaurant tax to the Revenue District Sekadau and also to see how much development targets and realization of hotel and restaurant taxes as well as to determine the strengths, weaknesses, opportunities and threats of the business hotel and restaurant in Sekadau. The method used is descriptive method, while the data used in this study are primary and secondary data on the contribution, targets and realization of hotel and restaurant tax. The strategy used by the author in answer to the problem of hotel and restaurant businesses are using SWOT analysis. Results of the analysis of the development of hotel and restaurant businesses in Sekadau through SWOT analysis can be concluded that the difference between the strengths and weaknesses of 0.32 and the difference between the opportunities and threats are of 0.34 means that the results of the discussion about the hotel and restaurant business The first quadrant is positioned yatitu favorable position. Based on the analysis QSPM, alternative strategies increased promotion of 5.17. development of hotel and restaurant business amounted to 6.17 and improved services and facilities of 5.00. The alternative strategy needs to be done is to conduct the development or construction of the hotel and restaurant business Sekadau region. Â  Keywords: Hotel and Restaurant Tax, Local Revenue, Enterprises Hotel and Restaurant.